ŉ Ondersoek na die rol van die "verwonde" kind in die werk van enkele kinder- en jeugverhaalskrywers in navolging van Alice Miller - Theron, Anke Salomie (Afrikaans and Netherlandic Studies, 2017)
This study focusses on the role of the wounded child in the writing process of authors who write children's and youth literature. The psychoanalytic theories of Alice Miller will be discussed with reference to a selection of her publications. Miller's theories are used to determine if the experiences and repressed emotions of an author's childhood play a role in their contextual and practical choices when writing children's literature. Miller's arguments and research about child abuse, the reliving process and the body's memory will be used as a theoretical framework. A contextual sample analysis on fairy tales will first be done, because it is considered an established form of children's literature. Hans Christian Andersen is used as a case study, due to the direct authorship of his fairy tales. In his case the theories of Melanie Klein will be used to complement those of Miller. This will be done in order to examine the role of Andersen's mother and grandmother within his fairy tales. The use of Klein's work is due to Miller's rejection of Freud. Klein incorporates Freud, whereas Miller rejects his concepts. Klein's theory will support Miller's as well as provide an additional perspective on child psychoanalysis. Selected characterisations and narratives within fairy tales will be singled out to demonstrate arguments from Miller's theories. The children's and youth literature of Fanie Viljoen, François Bloemhof and Verna Vels will be considered in order to determine if Miller's theories could deliver similar results as in the fairy tale sample analysis. Aspects which will be examined are the writing process, motivation for the creation of texts, prominent themes as well as practical choices surrounding narrative. Miller's concept of a "wounded" child will be examined in relation to the author and the writing process. The function of the wounded child and why Miller is the most appropriate reading strategy for children's and youth literature will be argued. To conclude, the actual goal of children's and youth literature and the most appropriate approach to it will be discussed. The practice of bibliotherapy will be presented as a practical example of the use of children's and youth literature. The point of this study is that the reliving process, to which Miller refers, results in the author returning to specific traumatic, embarrassing or extremely happy moments in his or her childhood. This process makes it possible to refer to a "wounded" child, where the profound nature of an experience points towards an ideal reader for which the writer creates the text.